PENGARUH ELECTRONIC WORD OF MOUTH DAN KEPERCAYAAN KONSUMEN TERHADAP NIAT BELI PRODUK DI SHOPEE INDONESIA - Adrieta Kirana Putri Are; Retno Setyorini (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2019)
Abstract, The purpose of this research is to find out and analyze how much the influence of Electronic Word of Mouth and consumer trust on product purchase intentions in Shopee Indonesia both simultaneously and partially. This research uses descriptive-causal research with quantitative research methods. Respondents in this study were 100 people, namely Shopee application users who had made purchases through e-commerce Shopee throughout Indonesia, using non-probability sampling methods. The results of this study indicate that there is significant simultaneous influence between Electronic Word of Mouth and consumer confidence in product purchase intentions in Shopee Indonesia by 21.8% while the remaining 78.2% is influenced by factors not examined in this study.